2014
DOI: 10.4102/sajr.v18i1.601
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of computed tomography angiography versus digital subtraction angiography in penetrating neck trauma at Groote Schuur Hospital, South Africa

Abstract: Background: Penetrating neck trauma is commonly encountered in South African trauma units, and is associated with high mortality and morbidity rates. The imaging protocol for stable patients with penetrating neck trauma remains controversial. There is only sparse data validating the use of computed tomography angiography (CTA) in the evaluation of penetrating neck trauma in South Africa.Objectives: To assess the sensitivity and specificity of CTA versus digital subtraction angiography (DSA) in detecting arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The majority of the full‐text reviewed articles were rejected for only reporting vascular injuries (LeBlang et al, 12 Munera et al, 13 Ofer et al, 14 Munera et al, 15 Stuhlfaut et al, 16 Hogan et al, 17 Kazi et al 18 ). Methodological concerns related to sampling bias were responsible for removing the articles by Scholtz et al, 19 Schroll et al, 20 Woo et al, 21 Osborn et al, 22 Siau et al, 23 and Bell et al 24 Missing data preventing the generation of 2×2 tables forced the removal of Maritz et al 25 and Ibraheem et al 26 Finally, the article by LeBlang et al 27 was removed for lack of CTA testing and the article by Morales‐Uribe et al 3 was a review article, leaving seven articles for our final review.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the full‐text reviewed articles were rejected for only reporting vascular injuries (LeBlang et al, 12 Munera et al, 13 Ofer et al, 14 Munera et al, 15 Stuhlfaut et al, 16 Hogan et al, 17 Kazi et al 18 ). Methodological concerns related to sampling bias were responsible for removing the articles by Scholtz et al, 19 Schroll et al, 20 Woo et al, 21 Osborn et al, 22 Siau et al, 23 and Bell et al 24 Missing data preventing the generation of 2×2 tables forced the removal of Maritz et al 25 and Ibraheem et al 26 Finally, the article by LeBlang et al 27 was removed for lack of CTA testing and the article by Morales‐Uribe et al 3 was a review article, leaving seven articles for our final review.…”
Section: Resultsmentioning
confidence: 99%
“…It requires mobilisation of theatre personnel, and it is performed in specialised centres. Although this imaging has been regarded as the gold-standard imaging modality for vascular trauma, in the modern practice, its role has been restricted to equivocal cases after CTA [ 33 ]. DSA has a high sensitivity and is preferred for diagnosis of penetrating cerebrovascular injuries (PCVI) since it has been demonstrated that CTA has lower sensitivity, specificity and positive and negative predictive values for the diagnosis of PCVI cerebrovascular injuries [ 34 ] (see Figure 2 ).…”
Section: Diagnostic Toolsmentioning
confidence: 99%